Perancangan Identifikasi Bahaya di Area Feed Water System Boiler Menggunakan Metode HAZOP (Hazard And Operability Study) - Saputra, Gilang; Supriyadi, Supriyadi; Dwiputra, Gerry Anugrah (Universitas Serang Raya, 2016)
Blast Furnace Complex is a new factory where there is no identification of potential hazards, the identification process of potential hazards also applies in the Feed water System area, which serves to continuously supply High Pressure Boiler Feed water as raw material for making Steam in Boilers. The process of identifying potential hazards aims to find out what potential hazards are found in the Feed water System area during work activities, so that preventive and risk control measures can be taken. This study uses the HAZOP (Hazard and Operability Study) method, which begins with determining the nodes, determining the operating parameters that occur at each node, then relying on guide words and the idea of the team to assess potential hazards, prevention that can be done and control efforts against potential hazards. . It was concluded from the results of the study that there were nine nodes with 11 operating deviations, of which all of the deviations were in the 9% Extreme Risk category, 18% for High Risk, 55% for Moderate Risk, and 18% Low Risk. for Extreme Risk is found at the Suction Pipe node HBF-CS4.0-11 with Less Pressure deviations caused by leakage on the HBF pipeline, with recommendations for patching at the point of leakage for emergency actions.